Implementation of Hidden Curriculum in the Formation of Religious Character (Multi-Case Study at SMA Muhammadiyah 1 and SMA Negeri 1 Gresik) - Amirudin, Noor; sutiah, Sutiah; marno, Marno; Supriyatno, Triyo (International Journal Labs, 2024)
The formation of religious character is the key to the success of educational institutions in producing graduates with integrity in the midst of global challenges. This success is not only determined by the formal curriculum, but also the implementation of a *hidden curriculum* that includes values, norms, and good practices in the school environment. This study aims to analyze the implementation model of *hidden curriculum* in the formation of religious character through a multi-case qualitative study with the Miles and Huberman analysis approach. The results of the study show three main findings. First, the concept of